Speech and audio signal processing processing and perception of speech and music - Gold, Bernard (John Wiley and Sons, 1999)
Speech and Audio Signal Processing provides the most current and comprehensive coverage of speech and audio signal processing available today. These topics include everything from basic foundation material on digital signal processing, pattern recognition acoustics, and hearing to material of historical significance not found anywhere else. The text also contains a range of applications of the technology, with strong focus on speech recognition and coding.